2019
DOI: 10.4102/sajr.v23i1.1732
|View full text |Cite
|
Sign up to set email alerts
|

Chest radiographs of cardiac devices (Part 2): Ventricular assist devices

Abstract: Heart failure is considered a worldwide pandemic affecting 26 million people globally. Patients who are unfit or waiting for cardiac transplantation may benefit from alternate mechanical support therapies using ventricular assist devices. It is not uncommon for radiologists, especially those working in institutions with a high volume of cardiac transplantations, to be presented with radiographs containing these devices. The role of the radiologist is not only to accurately identify these devices, but also to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…It is connected to the heart at the bottom of the ventricle where it draws oxygen-rich blood from the ventricle and pumps it to the aorta, where it flows to the rest of the body. Matthews et al (6) provide a very descriptive article on radiographs of VADs (Figure ).…”
Section: How Lvads Work Indications Special Exercise Considerationsmentioning
confidence: 99%
“…It is connected to the heart at the bottom of the ventricle where it draws oxygen-rich blood from the ventricle and pumps it to the aorta, where it flows to the rest of the body. Matthews et al (6) provide a very descriptive article on radiographs of VADs (Figure ).…”
Section: How Lvads Work Indications Special Exercise Considerationsmentioning
confidence: 99%
“…Importantly, patients with LVAD should not undergo magnetic resonance imaging due to the highly ferromagnetic component incompatibility [43].…”
Section: Additional Diagnostic Assessmentmentioning
confidence: 99%
“…8,16,17 Recently, it has been shown that correlations exist between computer tomography (CT) angles and radiographs 17 ; therefore, assessment and identification of pump position related risk factors can be easily accomplished by routine chest radiographs. 18 Even though, only two reports among HM3 patients linked death and heart failure readmission 19 or composite adverse events 20 to pump position.…”
Section: Introductionmentioning
confidence: 99%